Are climate and security policies coherent and integrated? A Policy Coherence Analysis - Schapendonk, Frans; Läderach, Peter R.D.; Pacillo, Grazia (2021)
This factsheet answers if climate and security policies coherent and integrated. The results show that there remains a practical disconnect between climate and peace and security-related policy fields. Furthermore, the analysis suggests that the research community should put an effort in creating policy-relevant and actionable understandings of what climate security and climate-peace opportunities mean, to enable policymakers across different contexts and scales to have a common understanding.